Streamlined β-Galactosidase Assay for Analysis of Recombinant Yeast Response to Estrogens - R. Le Guével; F. Pakdel (BioTechniques)
Here, we describe a rapid, convenient, and quantitative β-galactosidase assay in liquid culture of recombinant yeast that expresses the estrogen receptor. This assay allows large-scale screening of chemicals (more than 600 samples/day) for the evaluation of their direct estrogenic potency and accurate determination of their EC50 with minimal manipulations. The assay, which is based on digestion of the yeast cell wall by lyticase (zymolase), a β-glucanase isolated from Arthrobacter luteus, followed by a hypoosmotic shock lysis, is performed completely in 96-well plates. This protocol for using recombinant yeast with the two-hybrid technology significantly advances recombinant yeast manipulation.